2007
DOI: 10.1021/ma062941n
|View full text |Cite
|
Sign up to set email alerts
|

Comblike Liquid-Crystalline Polymers from Ionic Complexation of Dendronized Polymers and Lipids

Abstract: This work describes the self-assembly behavior, the structure, the state, and phase diagrams of comblike liquid-crystalline polymers obtained by supramolecular ionic complexation of cationic dendronized polymers (PG1-PG3) and anionic sulfonated lipid surfactants. In order to characterize the influence of both the polymer and the surfactant on the microphase separation of these complexes, dendronized polymers with generation 1 e n e 3, carrying 2 n positive charges per monomer, were complexed with a stoichiomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
77
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(91 citation statements)
references
References 44 publications
13
77
1
Order By: Relevance
“…These findings, which are in agreement with previously reported FTIR and NMR analysis, [13,14] allow a straightforward evaluation of the volume fraction of alkyl tails and dendronized polymers in final complexes, as soon as the densities of the individual components are measured.…”
Section: Transmission Electron Microscopysupporting
confidence: 91%
See 2 more Smart Citations
“…These findings, which are in agreement with previously reported FTIR and NMR analysis, [13,14] allow a straightforward evaluation of the volume fraction of alkyl tails and dendronized polymers in final complexes, as soon as the densities of the individual components are measured.…”
Section: Transmission Electron Microscopysupporting
confidence: 91%
“…First (PG1) and second (PG2) generation cationic dendronized polymers synthesized as described previously [13,14] were selected to form comb-like ionic supramolecular complexes as depicted in Figure 1. Complexation was realized in water solutions maintained at pH ¼ 3-4.…”
Section: Experimental Part Materials and Complex Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…choice of non-covalent bonding type(s), side-groups, and macromolecular template chemistry and architecture). 6 Regarding this last choice, much recent work has focused on complexes involving macromolecular templates with even more complicated architectures, such as dendrimers, 14,15 hyperbranched polymers, 16 dendronized polymers, [17][18][19] and rod-coil block copolymers. [20][21][22] Nandan et al have recently reported hierarchically organized materials formed by complexation of amphiphilic surfactants with heteroarm star (HAS) and block-arm star (BAS) polymers composed of polystyrene (PS) and poly(2-vinylpyridine) (PVP).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The hydrogen-bonding strategy has been applied mostly to linear homopolymers and block copolymers to design macromolecular templates in which the polymer backbone acts as a hydrogenbonding acceptor and surfactants act as hydrogen-bonding donors so that hairy comblike polymers are formed in which the segregation between the surfactant and the polymer backbone leads to the final morphology. 12 In the case of ionic complexation, various polyelectrolyte architectures have been considered, such as linear, hyperbranched, dendritic, and dendronized polymers, 8,13,14,15 while hydrocarbon-based surfactants and rigid rods have been the mostly investigated classes of ionic surfactants. 16,17 The resulting polyelectrolyte-surfactant complexes have been shown to microphase segregate into liquid crystalline mesophases, analogous to those obtained in systems where the mesogenic units are covalently attached to macromolecules.…”
Section: Introductionmentioning
confidence: 99%